2018
DOI: 10.1177/1362361318793409
|View full text |Cite
|
Sign up to set email alerts
|

What am I thinking? Perspective-taking from the perspective of adolescents with autism

Abstract: Autistic people are often described as being impaired with regards to theory of mind (ToM), though more recent literature finds flaws in the ToM deficit paradigm. Additionally, the predominant methods for examining ToM often rely on "observational" modes of assessment and do not adequately reflect the dynamic process of real-life perspective taking. Thus, it is imperative that researchers continue to test the autistic ToM deficit paradigm and explore ToM experiences through more naturalistic approaches. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 91 publications
1
22
0
Order By: Relevance
“…Several studies used the Heider and Simmel (1944) movie to investigate social perception among clinical groups, including individuals with an autism spectrum disorder (ASD), schizophrenia, and patients with lesions to the amygdala. These studies have found strikingly impoverished or inappropriate descriptions in the clinical groups, supporting the idea that these individuals have a deficit in theory of mind (ToM) (Russell, Reynaud, Herba, Morris, & Corcoran, 2006; but see Atherton, Lummis, Day, & Cross, 2018, for an alternative view).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Several studies used the Heider and Simmel (1944) movie to investigate social perception among clinical groups, including individuals with an autism spectrum disorder (ASD), schizophrenia, and patients with lesions to the amygdala. These studies have found strikingly impoverished or inappropriate descriptions in the clinical groups, supporting the idea that these individuals have a deficit in theory of mind (ToM) (Russell, Reynaud, Herba, Morris, & Corcoran, 2006; but see Atherton, Lummis, Day, & Cross, 2018, for an alternative view).…”
Section: Introductionmentioning
confidence: 69%
“…Although the narrative task has consistently yielded less appropriate description in some clinical populations, the requirement to verbalise the response complicates the findings (Gao, Newman, & Scholl, 2009). First, relying on verbal report means that only individuals with sufficient language skills can participate (Atherton et al, 2018). Second, as in other verbal report tasks, standardising task administration is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Although the validity of the ToM hypothesis has been questioned recently (in terms of whether people with autism demonstrate a deficit or a difference in the way they process social information; Atherton et al, 2019), difficulties with ToM remains one of the widely referenced cognitive theories to explain why individuals with autism show distinct differences in English language usage. Researchers have theorized that ToM and associated perspective taking skills are necessary for the comprehension and production of personal and ambiguous pronouns because they require the speaker to understand and shift perspectives between themselves and others (Arunachalam & Luyster, 2018; Kuijper et al, 2015).…”
Section: Broad Language Development and Pronoun Acquisition In Indivimentioning
confidence: 99%
“…To date, central pillars of theories suggesting the importance of mentalizing for everyday social interaction and a link between mentalizing, autistic traits, and actual social behavior remain under-researched. On the one hand, our knowledge about mentalizing in people with and without autism stems almost exclusively from lab-based research (c.f., Atherton, Lummis, Day, & Cross, 2018). On the other hand, social interaction outside the lab is usually assessed indirectly via interviews or questionnaires (e.g., Kreider et al, 2016).…”
mentioning
confidence: 99%
“…Only a handful of studies have addressed the impact of social cognitive deficits of individuals with autism on their everyday social life (Atherton et al, 2018;e.g., Begeer, Malle, Nieuwland, & Keysar, 2010;Chen, Bundy, Cordier, Chien, & Einfeld, 2016;Frith, Happé, & Siddons, 1994). Consequently, there is a large gap between the solid empirical basis of mentalizing characteristics in the lab and knowledge about actual social interaction in everyday lives of people with and without autism.…”
mentioning
confidence: 99%